2013
DOI: 10.1016/j.carbon.2013.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of carbon nanocoil forests on BaSrTiO3 substrates with the aid of a Sn catalyst

Abstract: A B S T R A C TA simple route for the Sn-assisted synthesis of carbon nanocoils (CNCs) by chemical vapor deposition of acetylene on polycrystalline BaSrTiO 3 (BST) substrates is reported. In this study, high-quality CNC forests have been synthesized on BST substrates with the presence of Sn. The morphologies and qualities of the CNCs were characterized by scanning electron microscopy, transmission electron microscopy, and Raman spectroscopy, while the structures and compositions of catalysts were investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…4a. It is found that the height of CNC layer continuously increased with growth time, and the maximum thickness of the CNC layer reaches 306 μm after the reaction for 6 h. This is the highest value compared with those reported recently [34][35][36][40][41][42]. It is noted that both curves of the yield and thickness versus time are well matched, suggesting that the carbon deposits are almost CNCs.…”
Section: Yield Of High-purity Cncssupporting
confidence: 56%
See 2 more Smart Citations
“…4a. It is found that the height of CNC layer continuously increased with growth time, and the maximum thickness of the CNC layer reaches 306 μm after the reaction for 6 h. This is the highest value compared with those reported recently [34][35][36][40][41][42]. It is noted that both curves of the yield and thickness versus time are well matched, suggesting that the carbon deposits are almost CNCs.…”
Section: Yield Of High-purity Cncssupporting
confidence: 56%
“… Catalysts Preparation method Purity a Economy b Thickness of carbon layer (μm) Yield Refs. 1 Ag/K Thermal evaporation Good Fair Several microns [ 35 ] 2 Au/K Thermal evaporation Good Fair Several microns [ 34 ] 3 Cu ALD Excellent Fair Few [ 28 ] 4 BaSrTiO 3 /Sn Mechanical mixing Excellent Fair Few [ 36 ] 5 Na/K Solution method Good Good 1178% [ 37 ] 6 Fe Sol–Gel method Excellent Fair Few 8078% [ 23 ] 7 Fe/In/Sn …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, many studies related to catalyst for growth of CNCs have been conducted to develop highly efficient catalysts for CNC growth based on transition-metal based catalysts, including the use of Co, Fe, and Ni [1,2], and multicomponent-catalysts such as Fe/Sn, Fe/In/Sn alloys [8,[13][14][15][16], and K/Ag [17]. Aside from these efforts for the development of catalysts, the interaction between the substrate and catalyst reportedly affects CNC growth [18][19][20]. The additional Sn buffer layer strongly supports the formation of highly efficient catalytic particles at the very early stage of CNC growth, which results in the high yield synthesis of CNCs.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al [36] reported synthesizing single helical CNCs with 200-900 nm of external coil diameter using Sn on BaSrTiO3 substrate as catalyst. Sn was introduced in the pits or grain boundary triple junctions of polycrystalline BaSrTiO3 substrate.…”
Section: Sn Catalyst Supported By Basrtio3 Substratementioning
confidence: 99%